2010
DOI: 10.1111/j.1574-6968.2010.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of phenotypic and genotypic methods for the determination of the biofilm-forming abilities of Staphylococcus epidermidis

Abstract: The collection of 146 Staphylococcus epidermidis strains isolated from the nasopharynx of lung cancer patients has been studied for the ability of slime secretion and biofilm formation using the Congo red agar (CRA) test and the microtiter plate (MtP) method, respectively. The prevalence of the icaAD and the aap genes was also analyzed. Some isolates (35.6%) were biofilm positive by the MtP method, while 58.9% of isolates exhibited a slime-positive phenotype by the CRA test. The sensitivities of the CRA test e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
4
32
2
Order By: Relevance
“…By this assay, we found that biofilm formation was widespread amongst both commensal and nosocomial S. epidermidis isolates. The ica genes, encoding biofilm-associated genes for poly- N -acetylglucosamine synthesis, were found in only 60% of the biofilm-forming commensal isolates, in agreement with previous studies [31]. This suggests genetic heterogeneity underlying the mechanism by which S. epidermidis forms a biofilm.…”
Section: Resultssupporting
confidence: 90%
“…By this assay, we found that biofilm formation was widespread amongst both commensal and nosocomial S. epidermidis isolates. The ica genes, encoding biofilm-associated genes for poly- N -acetylglucosamine synthesis, were found in only 60% of the biofilm-forming commensal isolates, in agreement with previous studies [31]. This suggests genetic heterogeneity underlying the mechanism by which S. epidermidis forms a biofilm.…”
Section: Resultssupporting
confidence: 90%
“…The detection of biofilm production among the strains of S. aureus was performed by microtiter plate method [11]. The S. aureus was grown in 96 welled microtiter plate containing trypticase soya broth with 2% glucose, at 35 °C for 48 h. The optical density value of the bacteria that coat the wall of the wells was determined with the help of enzyme linked immunosorbent assay reader after staining with crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…3). This result was not necessarily surprising, as our experience and that of others (53,66,73) suggests in vitro static biofilm assays essentially measure PIA synthesis and a hallmark of 1457 is constitutive production of PIA (9,49,53). Therefore, to determine the contribution of Aap in biofilm accumulation in the absence of PIA, bacteriophage 71 was used to transduce the aap::tetM marker from 1457 ⌬aap into 1457 ⌬ica (53), generating 1457 ⌬ica ⌬aap.…”
Section: Construction and Preliminary Characterization Of An Isogenicmentioning
confidence: 85%
“…Microtiter plate assays were based on the procedure of Christensen et al, with modifications (65,66). Overnight planktonic cultures were diluted 1:100 in fresh TSB.…”
Section: Methodsmentioning
confidence: 99%